(untitled) (Journal of Oriental Studies, 2018)
This article examines some of the factors in the Confucian tradition that have affected the economic success of the Republic of Korea. The teaching of Confucius was the main teaching, which had a great influence on the formation of Korean consciousness, the behavior of the system of thinking and way of life for thousands of years. In the 60s of the twentieth century, it played an important role in the economic development strategies of the state. The traditional political system in Korean society allowed the state to pursue a strict social policy. The special hard work, special hard work, endurance and mobility of people at that time made a great contribution to the economic achievement of South Korea.